رسول اللہ ﷺ سے حیوانات کا کلام اور مطالعہ سیرت میں اس کی اہمیت: Communication of Animals with the Holy Prophet ﷺ & it’s Significance in the Study of Biography - Paracha, Dr. Kulsoom; Ameer, Rowaifa (Al-Amīr Research Journal for Islamic Studies, 2024)
In the final celestial book of Allah, the Hadith Sharif, and the biography (Sirah) of the Prophet Muhammad ﷺ, numerous events highlight the special status granted to the Seal of the Prophets, Muhammad Mustafa Ahmad Mujtaba ﷺ. As the ultimate guide and exemplary teacher, he was sent to illuminate the path of righteousness, not only for this world but for all realms. His entire 63-year life—his actions, thoughts, character, and every external and internal aspect—stands as a flawless model, devoid of any imperfection, and shines as clearly as the light of day. Among the unique occurrences within the Prophet’s life are remarkable accounts of animals communicating with him, which emphasize his noble status and divine connection. Some animals bowed in reverence, others expressed grievances against their owners, and some bore witness to his Prophethood, symbolizing the respect and awareness even non-human creatures held towards him. This study explores these narratives, examining the significant episodes of animals interacting with the Messenger of Allah ﷺ and the theological and moral lessons conveyed through these interactions. Keywords: Prophet Muhammad ﷺ, Islamic teachings, animals, Prophethood, Sirah, miracles, communication, divine signs